Pt Single Atoms on TiO2 Can Catalyze Water Oxidation in Photoelectrochemical Experiments - Wu, Siming; Wu, Lu; Denisov, Nikita; Badura, Zdenek; Zoppellaro, Giorgio; Yang, Xiao Yu; Schmuki, Patrik (Journal of the American Chemical Society, 2024)
Photoelectrochemical water splitting on n-type semiconductors is highly dependent on catalysis of the rate-determining reaction of O2 evolution. Conventionally, in electrochemistry and photoelectrochemistry O2 evolution is catalyzed by metal oxide catalysts like IrO2 and RuO2, whereas noble metals such as Pt are considered unsuitable for this purpose. However, our study finds that Pt, in its single-atom form, exhibits exceptional cocatalytic properties for photoelectrochemical water oxidation on a TiO2 photoanode, in contrast to Pt in a nanoparticle form. The decoration of Pt single atoms onto TiO2 yields a remarkable current density of 5.89 mA cm-2 at 1.23 VRHE, surpassing bare TiO2 (or Pt nanoparticle decorated TiO2) by 2.52 times. Notably, this enhancement remains consistent over a wide pH range. By accompanying theoretical work, we assign this significant enhancement to an improved charge transfer and separation efficiency along with accelerated kinetics in the oxygen evolution reaction facilitated by the presence of Pt single atoms on the TiO2 surface.
CRIS-Team Scopus Importer:2024-06-21